Bentuk Penyajian Tari Pilanuk di Kecamatan Sungai Ambawang Kabupaten Kubu Raya Kalimantan Barat - Desi Susilawati; Regaria Tindarika; Dwi Oktariani (SENDRATASIK UNP, 2023)
The background of this research is because of the researcher's concern about the authenticity of the Pilanuk Dance performance, which in the future will experience changes. Therefore the researcher describes and documents the Pilanuk Dance in the form of videos, writings, pictures. This study uses descriptive methods, qualitative research forms, ethnochoreological approaches and choreographic approaches. Data collection techniques in the form of observation techniques, interview techniques, and documentation techniques. The technique to test the validity of the data used is the extension of observations and source triangulation. Based on the data analysis, it was concluded that the form of presentation of the Pilanuk Dance has a movement structure, namely the opening movement, the core movement which consists of agile footsteps and closing movements. The number of dancers must be even, namely 8 and so on. This dance can be danced by both men and women. The floor pattern is in the form of straight lines, circles and plus signs which are interpreted as the direction of the compass. drum). The costumes used by female dancers are traditional Dayak Kanayant clothes, skirts, shawls, headbands, roof tiles, obi/belts, necklaces, earrings, rinyuakng leaves. For male costumes, they use loincloths, scarves, headbands, tiles, necklaces, rinyuakng leaves, obi/belt. The facial makeup used by dancers is natural makeup. The place for the performance uses an open stage or the hall of a traditional house.